Pengaruh massa air baku terhadap performansi sistem destilasi - Catrawedarma, IGNB. (Jurnal Energi Dan Manufaktur, 2012)
Clean water is requirement of very important human life. One of the method to be used for obtain clean water is destillation process. Important matter in destillation process is evaporation and condensation process, influenced by heating of standard water. Heating process of this standard water will influence by mass of standard water to be heated. Mass standard water which many will cause heating process become requiring long time, so that from that thing is conducted by examination with variations of mass standard water in basin. Examination conducted to get data which in the form of mass and temperature condensat which is accomodated in reservoa. For the next, from the data conducted by calculation to know performance of destillation sistem which it form are destillation rate, product efficiency, and system efficiency for the variations of mass standard water. From result of data analysis and calculation, can know that happened fluctuation of system efficiency and destillation rate. System efficiency depended from ratio between condensation energi (qc) of energi enter system (qin). Destillation rate depended from condensat mass ratio a time difference. From result of calculation got that variation of 3 kg standard water giving the best value from is fifth of standard water mass variation of with value : destilas rate average equal to 3,829 gr/mnt, total product efficiency equal to 80,42 %, and total efficiency average equal to 22,67 %.
Keywords: Variation of mass standard water, fast of destillation, efficiency of product, and efficiency of system.